2021
DOI: 10.1177/03091333211055850
|View full text |Cite
|
Sign up to set email alerts
|

Why can China maintain a high crop diversity? A spatial-temporal dynamic analysis

Abstract: Crop diversity is crucial for producing more food and nutrition in the crowded planet and achieving agricultural sustainable development, and thus it is a hot topic in shaping policies aimed at ensuring food security. Many studies have revealed that enhanced crop diversity can benefit crop productivity. However, research on how to maintain a relatively high crop diversity at regional and national scales remains limited. This study attempts to examine the underlying mechanisms of crop diversity changes in China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Only a few studies have assessed the relationships between irrigation and diversification at national levels. Studies from Slovakia [47] and the United States [82] found irrigation expansion led to greater CSD, while a study from China instead found it instead led to specialized monocropping [12]. In general, national-level understanding of the relationship is insufficient, which has served as a barrier to effective policies [83].…”
Section: Irrigation Enhances Crop Species Richness and Evenness Diver...mentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies have assessed the relationships between irrigation and diversification at national levels. Studies from Slovakia [47] and the United States [82] found irrigation expansion led to greater CSD, while a study from China instead found it instead led to specialized monocropping [12]. In general, national-level understanding of the relationship is insufficient, which has served as a barrier to effective policies [83].…”
Section: Irrigation Enhances Crop Species Richness and Evenness Diver...mentioning
confidence: 99%
“…Enhancing crop diversity is now a core component of agri-environmental policies around the world, including multiple initiatives of the Food and Agriculture Organization of the United Nations [10,11]. Despite this policy focus, many of the drivers of crop diversification are poorly understood [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…When leading to diversification, farmers use irrigation to expand the range of crops that can be grown, which often includes more value-added or nutritionally diverse crops [47,48]. When leading to specialization, farmers instead use irrigation to enhance the productivity of a few, usually water-intensive species [49,50]. Ultimately, farmer decisions over how to employ irrigation to diversify or specialize derive from perceptions of the opportunities and constraints of socioeconomic, environmental, and other factors [51,52].…”
Section: Crop Species Diversity Dependent On Unsustainable Irrigation...mentioning
confidence: 99%